Cooke's index: A simple, cost-effective method for multiple practitioners to estimate European rabbit abundance. (June 2023) - Delibes-Mateos, Miguel; Castro, Francisca; Arias de Reyna, Luis; Camacho, Agustín; Cooke, Brian; Villafuerte, Rafael
Highlights: Cooke's method scores European rabbit abundance according to the sightings of pellets. It provides a simple and accurate way to estimate the relative abundance of rabbits. It is inexpensive and is accessible for non-expert land managers worldwide. It may be used in a wide range of habitats and scales. Abstract: The development of evidence-based tools that help to monitor wildlife populations is essential to assess the success of management interventions. Here, we evaluated the reliability of a simple method to estimate the abundance of the European rabbit ( Oryctolagus cuniculus ), which is likely one of the most managed vertebrate species worldwide. Cooke's method involves noting the distribution and frequency of sightings of rabbit fecal pellets and accordingly scoring the abundance of rabbits on a scale 0–5. To assess its reliability, we used information collected during 101 rabbit surveys conducted across mainland Spain during the summer of 2022. In each 4-km walked transect, we estimated rabbit abundance using Cooke's method every 400 m (i.e., 10 indexes), and pellet counts (2 plots per 100 m walked, i.e., 80 counts), which were used as a reference index. Our results revealed a strong correlation between the estimates of rabbit abundance obtained using Cooke's method and the number of pellets counted per m 2 regardless of the statistical approach used. This suggests that Cooke's method provides a simple and inexpensive way of estimating the abundance of European rabbits, which we believe that can be very useful for non-expert land managers after a very short training period. Importantly, our findings demonstrate that it is reliable to estimate rabbit abundance in different land uses. In addition, Cooke's method can be used in different seasons, is not affected by circadian activity of rabbits, seems to work well across the whole range of rabbit abundance, and may be useful for estimating rabbit abundance at different spatial scales. As everyday people rather than scientists are generally involved in managing European rabbits, we strongly recommend this simple method that allows rabbit abundance to be quickly estimated so that management decisions can be made. More broadly, we encourage researchers to investigate the usefulness of similar monitoring tools for other mammal species that are often surveyed through counting their pellets.